Judging Incumbents' Character: The Impact of Scandal. Issue 3 (3rd July 2019) - Basinger, Scott J.
Abstract : This article uses panel survey data from 2010 to 2012 to examine how scandals affect perceptions of House incumbents' character. Scandals negatively impact impressions of the incumbent's integrity, indicating that voters incorporate information about their representatives' behavior. Scandals' effects on attitudes are shown to vary depending on the type of misbehavior that is alleged, with sex scandals having far deeper and wider impact than other types of scandals. Scandals significantly influence the vote choice, although impressions of the incumbent's integrity mediate more than one-third of their effect.